Development of a Novel Innovative Umbrella Falsework System for Concrete Slabs - Hashim, Abdelazem (AUC Knowledge Fountain, 2026)
Formwork is one of the major elements that contribute to the cost and duration of concrete building projects. This is why optimizing such an element can lead to huge savings to all parties involved in the construction projects. With contractors facing huge challenges in such a competitive industry and employers seeking the least price and least duration for their projects, contractors are constantly under the obligations of finding the best alternatives to deliver their projects in terms of both time and money. Therefore, the main aim of this research project is to develop a falsework system, where the falsework system is considered the base of the entire temporary formwork structure, which possesses parameters that are competitive to other commercially available systems, in terms of their effect on construction projects cost and duration. This study proposes a novel falsework system to support concrete slabs up to 250 mm thick. The developed falsework system resembles an umbrella in its structure and its opening and closing mechanism, and therefore has been named the umbrella falsework system (UFS). The UFS is composed entirely of steel. To design such a system, a composite methodology has been followed, where analytical modeling and theoretical design provisions of the Egyptian Code of Practice for Steel Constructions have been complemented by practical fabrication and prototype experimentation in two cycles that were followed by a detailed finalized design. To validate the efficiency of the UFS, it has been compared to other commercially available systems produced by well-known formwork companies in the Egyptian market. The key parameters of evaluation of the different systems were their weight, cost, erection duration, consumed volume and sustainability aspects per unit area of the supported slab, where the UFS has successfully secured a spot in the top two ranks across all parameters, which validates its efficiency towards adding value to the construction industry.